Systematic Review of Level 1 Evidence for Laparoscopic Pediatric Surgery: Do Our Procedures Comply with the Requirements of Evidence-Based Medicine? - Dingemann, Jens; Ure, Benno M. (European Journal of Pediatric Surgery, 2013)
Introduction Laparoscopic techniques have evolved quickly in recent years and are regarded as standard procedures in pediatric surgery today. However, most studies comparing laparoscopic operations with the corresponding open procedure do not reach a high level of evidence according to the criteria of the Oxford Centre for Evidence-Based Medicine. For evidence Level 1a, a meta-analysis (MA) of different randomized controlled trials (RCTs) is required. For evidence Level 1b, at least one RCT is required. The aim of our study was to evaluate the availability of Level 1 studies comparing laparoscopic procedures with the corresponding open operation in pediatric surgery.Materials and Methods Systematic review of clinical Level 1 studies using PubMed. All MA and RCT were identified and individually reviewed. Only studies comparing pediatric laparoscopic procedures with the corresponding open operation were included. RCTs included in MA were only individually analyzed if they focused on additional endpoints. Endpoints of the study were advantages and disadvantages of laparoscopy compared with the open operation.Results A total of 20 manuscripts met the inclusion criteria (9 MA and 11 RCT). Studies providing evidence Level 1a were identified for five types of laparoscopic procedures (laparoscopic appendectomy, inguinal hernia repair, orchidopexy, pyloromyotomy, and varicocelectomy). Studies providing evidence Level 1b were identified for two types of laparoscopic procedures (fundoplication and pyeloplasty). The advantages of laparoscopy were less wound infections, ileus and postoperative pain (appendectomy), less retching (fundoplication), lower incidence of metachronous inguinal hernia, shorter hospital stay (appendectomy, orchiopexy, and pyeloplasty), and shorter time to full feeds (pyloromyotomy).Conclusion Studies providing evidence Level 1 are only available for seven laparoscopic procedures in pediatric surgery. Effort has to be made to extend the existing Level 1 evidence and to gain high level evidence for further laparoscopic procedures.
Keywords: laparoscopic surgery; evidence-based medicine; children; meta-analysis; randomized controlled trial